Modelling the accumulation of 137Cs by Atlantic bluefin tuna (Thunnus thynnus) after a hypothetical nuclear accident in the Northwest Atlantic Ocean - Carmen Cortés; Raúl Periáñez; Barbara A. Block; Michael R. Castleton; Pablo Cermeño; Simon Dedman (Journal of Marine Systems, 2026)

Deep diving behaviour in oceanic manta rays and its potential function - Calvin S. Beale; Ferawati Runtuboy; Abraham B. Sianipar; Angela J. E. Beer; Kadarusman; Mark V. Erdmann; Edy Setyawan; Lydia Green; Clinton A. J. Duffy; Samantha Andrzejaczek; Barbara A. Block; Kerstin Forsberg; et al. (Frontiers in Marine Science, 2025)
Deep dives are performed by a range of marine megafauna, yet their function remains poorly understood. Proposed functions include foraging, predator avoidance, and navigation, but limited fine-scale data have hindered rigorous testing of these hypotheses. Here, depth time-series data from eight recovered and 16 non-recovered satellite tags deployed on oceanic manta rays ( Mobula birostris ) in Indonesia, Peru, and New Zealand were examined to characterise extreme dives and identify their potential function. From a total of 46,945 dives, 79 extreme dives (>500 m) were recorded, 11 of which were documented from recovered tags and associated high sampling frequency. Extreme dives were distinguished by rapid descents (up to 2.9 m s⁻¹), brief horizontal “steps” at depth, gradually slowing ascents, and extended periods spent near the surface both before and after diving. Unlike typical foraging dives, no substantial bottom phase was observed, and vertical oscillations—expected if feeding at depth—were absent. Extreme dives also occurred more frequently with increasing distance from the continental shelf edge as well as preceding periods of high 72h distance travelled, indicating they may inform subsequent movements. We propose that extreme dives enable oceanic manta rays to survey the properties of the water column, likely gathering environmental cues—such as temperature, dissolved oxygen, or geomagnetic gradients—to guide navigation and/or the decision to leave or remain in a general area. In open-ocean environments where external reference points are absent, such costly but infrequent dives may provide critical information for long-distance movements. Our results offer new insights into the role of extreme diving behaviour in oceanic manta rays and highlight the importance of fine-scale data for understanding deep-diving behaviours in marine megafauna.

A classification system for wounds and scars observed on white sharks (Carcharodon carcharias) - Scot D. Anderson; Paul E. Kanive; Taylor K. Chapple; Samantha Andrzejaczek; Barbara A. Block; Salvador J. Jorgensen (Frontiers in Marine Science, 2025)

Multi‐Species Telemetry Quantifies Current and Future Efficacy of a Remote Marine Protected Area - Morgan E. Gilmour; Kydd Pollock; Josh Adams; Barbara A. Block; Jennifer E. Caselle; Alex Filous; Alan M. Friedlander; Edward T. Game; Elliott L. Hazen; Marie Hill; Nick D. Holmes; Kevin D. Lafferty; et al. (Global Change Biology, 2025)
Large‐scale marine protected areas (LSMPAs; > 1000 km 2 ) provide important refuge for large mobile species, but most do not encompass species' ranges. To better understand current and future LSMPA value, we concurrently tracked nine species (seabirds, cetaceans, pelagic fishes, manta rays, reef sharks) at Palmyra Atoll and Kingman Reef (PKMPA) in the U.S. Pacific Islands Heritage Marine National Monument. PKMPA and the U.S. Exclusive Economic Zone encompassed 39% and 54% of species movements ( n = 83; tracking duration range: 0.5–350 days), respectively. Species distribution models indicated 73% of PKMPA contained highly suitable habitat. Under two projected future scenarios (SSP 1–2.6, “Sustainability”; SSP 3–7.0, “Rocky Road”), strong sea surface temperature gradients initially could cause abrupt oceanic change resulting in predicted habitat loss in 2040–2050, followed by an equilibrium response and regained habitat by 2090–2100. Current and future suitable habitats were available adjacent to PKMPA, suggesting that increased MPA size could enhance protection. Our three‐tiered approach combining animal tracking with publicly available remote sensing data and future projected environmental scenarios could be used to design, study, and monitor protected areas throughout the world. Holistic approaches that encompass diverse species and habitat use can enhance assessments of protected area designs. Animal telemetry and remote sensing may be helpful for ascertaining the extent to which other MPAs protect large mobile species in the future.

Lunar cycle effects on pelagic predators and fisheries: insights into tuna, billfish, sharks, and rays - Samantha Andrzejaczek; Alexandra E. DiGiacomo; Chloe S. Mikles; Camille M. L. S. Pagniello; Theodore E. J. Reimer; Barbara A. Block (Reviews in Fish Biology and Fisheries, 2025)

First satellite track of a juvenile shortfin mako shark (Isurus oxyrinchus) in the Mediterranean Sea - Brendan D. Shea; Taylor K. Chapple; Khaled Echwikhi; Chiara Gambardella; Jeremy F. Jenrette; Stefano Moro; Robert J. Schallert; Barbara A. Block; Francesco Ferretti (Frontiers in Marine Science, 2024)

Numerical modelling of radionuclide uptake by bluefin tuna along its migration routes in the Mediterranean Sea after a nuclear accident - Carmen Cortés; Raúl Periáñez; Barbara A. Block; Michael R. Castleton; Pablo Cermeño; Simon Dedman (Marine Environmental Research, 2024)

On the tracks of white sharks in the Mediterranean Sea - Francesco Ferretti; Brendan D. Shea; Chiara Gambardella; Jeremy F. Jenrette; Stefano Moro; Khaled Echwikhi; Robert J. Schallert; Austin J. Gallagher; Barbara A. Block; Taylor K. Chapple (Frontiers in Marine Science, 2024)
White sharks ( Carcharodon carcharias ) are among the most widespread, charismatic, and studied predators in the ocean. However, their conservation status is concerning in many ocean sectors, most notably the Mediterranean Sea, which hosts one of the least known and most endangered populations globally. Though they were historically abundant and widely distributed in the region, Mediterranean white sharks have declined to dangerously low abundance levels, impacted by centuries of coastal and, more recently, industrial fishing. The IUCN lists this species as Critically Endangered in the region, but information about its current abundance and ecology is scarce, hindering effective management and conservation. Here, we describe our initial effort to find and track the remaining Mediterranean white sharks and report what we have learned from these activities. In 2021-2023, we conducted three pilot expeditions in the Sicilian Channel, covering four major sites, collecting 159 eDNA samples, and carrying out 359 hrs of pelagic mid-water baited video surveys, 43 hours of deep-water benthic baited video surveys, and 111 hrs of fishing. Baited video surveys detected 42 species of bony fishes, elasmobranchs, marine mammals, and turtles. We detected white sharks at four sites from eDNA samples. Though we did not observe white sharks directly, these activities supported the identification of one of the last strongholds of this population in the region and started a multi-institutional white shark conservation program in the Mediterranean Sea, aiming to track the last white sharks in the region, estimate their abundance and extinction risk, characterize the species’ ecology and inform management and conservation.

A framework for optimising opportunistic collaborative syntheses to propel ecological conservation - Ana M.M. Sequeira; Amanda E. Bates; Graeme Hays; David W. Sims; Samantha Andrzejaczek; Asta Audzijonyte; Julia K. Baum; Martin Beal; Barbara Block; Joshua Cinner; Kaitlyn Cowley; Eric Gilman; et al. (Biological Conservation, 2024)

Global habitat predictions to inform spatiotemporal fisheries management: Initial steps within the framework - Heather D. Bowlby; Jean-Noël Druon; Jon Lopez; Maria José Juan-Jordá; María Teresa Carreón-Zapiain; Frederic Vandeperre; Agostino Leone; Brittany Finucci; Philippe S. Sabarros; Barbara A. Block; Haritz Arrizabalaga; Pedro Afonso; et al. (Marine Policy, 2024)

Satellite tagging insights into the seasonal movements and behavior of Mediterranean spearfish (Tetrapturus belone, Istiophoridae) - Danilo Malara; Pietro Battaglia; Martin C. Arostegui; Jonathan J. Dale; Barbara A. Block; Camrin D. Braun; Massimo Brogna; Silvestro Greco; Teresa Romeo (Frontiers in Marine Science, 2024)
The Mediterranean spearfish ( Tetrapturus belone ) is a highly migratory predator, also exploited by commercial and recreational fisheries although its catches are poorly reported. The fishing pressure on this species is currently unknown because catch and landing data are fragmentary. Furthermore, more ecological information (e.g. migratory movements) is needed to establish eventual management measures, and ICCAT has not examined the population status yet. Understanding species migratory movements is crucial for addressing conservation challenges and supporting management decisions. In this study we investigated the migratory movements, seasonal patterns, vertical behavior, and thermal preference of T. belone , with the aim to improve information on its ecology and behavior. Overall, six individuals were tagged in the Strait of Messina and Tyrrhenian Sea with pop-up satellite tags and their movements were mainly restricted to the central Mediterranean. Utilization distributions derived from geolocation revealed an overall and seasonal importance of the Tyrrhenian Sea and Strait of Sicily, as well as variability in winter habitat use. While the fish exhibited similar depth preference, spending the majority of time at depths ≤ 10 m, we observed that the Mediterranean spearfish is also able to perform sporadic deep dives below 200 m. Vertical movement showed a bimodal pattern common in other billfish species, characterized by occupation of shallower, warmer waters during the night and deeper, cooler waters during the day. This research increases knowledge on the migration ecology and habitat preference of T. belone which is important for management of this understudied species.

Tagging of Atlantic bluefin tuna off Ireland reveals use of distinct oceanographic hotspots - Camille M.L.S. Pagniello; Niall Ó Maoiléidigh; Hugo Maxwell; Michael R. Castleton; Emilius A. Aalto; Jonathan J. Dale; Robert J. Schallert; Michael J.W. Stokesbury; Ronán Cosgrove; Simon Dedman; Alan Drumm; Ross O'Neill; et al. (Progress in Oceanography, 2023)

Connectivity between white shark populations off Central California, USA and Guadalupe Island, Mexico - Paul E. Kanive; Jay J. Rotella; Taylor K. Chapple; Scot D. Anderson; Mauricio Hoyos-Padilla; Abbott Peter Klimley; Felipe Galván-Magaña; Samantha Andrzejaczek; Barbara A. Block; Salvador J. Jorgensen (Frontiers in Marine Science, 2023)
Marine animals often move beyond national borders and exclusive economic zones resulting in a need for trans-boundary management spanning multiple national jurisdictions. Highly migratory fish vulnerable to over-exploitation require protections at international level, as exploitation practices can be disparate between adjacent countries and marine jurisdictions. In this study we collaboratively conducted an analysis of white shark connectivity between two main aggregation regions with independent population assessment and legal protection programs; one off central California, USA and one off Guadalupe Island, Mexico. We acoustically tagged 326 sub-adult and adult white sharks in central California (n=210) and in Guadalupe Island (n=116) with acoustic transmitters between 2008-2019. Of the 326 tagged white sharks, 30 (9.20%) individuals were detected at both regions during the study period. We used a Bayesian implementation of logistic regression with a binomial distribution to estimate the effect of sex, maturity, and tag location to the response variable of probability of moving from one region to the other. While nearly one in ten individuals in our sample were detected in both regions over the study period, the annual rate of trans-regional movement was low (probability of movement = 0.015 yr -1 , 95% credible interval = 0.002, 0.061). Sub-adults were more likely than adults to move between regions and sharks were more likely to move from Guadalupe Island to central California, however, sex, and year were not important factors influencing movement. This first estimation of demographic-specific trans-regional movement connecting US and Mexico aggregations with high seasonal site fidelity represents an important step to future international management and assessment of the northeastern Pacific white shark population as a whole.

Assignment of tracks from tagged Atlantic bluefin tuna Thunnus thynnus to potential stocks using behavioural differences and habitat partitioning - Simon Dedman; Emilius A. Aalto; Michael J. W. Stokesbury; Robert J. Schallert; Michael R. Castleton; Barbara A. Block (Frontiers in Marine Science, 2023)
Introduction Atlantic bluefin tuna (ABT) are large, migratory pelagic predators of high economic importance. ABT are currently managed as two independent stocks assigned to discrete spawning areas (Gulf of Mexico, and Mediterranean); however, stock overlap outside spawning areas makes accurate assignment of catch to stock-of-origin difficult. Methods Within this two-stock paradigm, we characterised stock-specific spatial distributions and behaviours by comparing habitat usage and vertical movement behaviours of 118 electronically tagged adult ABT spatially assigned to the GOM and Med spawning grounds. These spatial and behavioural differences were used in tests to probabilistically assign unknown individuals (which did not visit the GOM/Med spawning areas) to a stock. Results This new methodological approach using existing tag data, enables increased assignment of a track to a potential stock, to be achieved before genetic assignments. We identified certain markedly different movement patterns, range extents, depth use preferences (and associated area usage), migration directness and speeds, corresponding distance from shore, and mesopelagic-layer visitation. The probabilistic assignment approach had 97% in-bag testing accuracy, then assigned 190 individuals to a stock, doubling the number of assigned stock-of-origin tracks in our dataset, and potentially revealing novel movement and behaviour patterns among pre-spawning-age ABT. Discussion This approach can be easily adapted to other study species, more stocks, and different testing variables, hopefully serving as a useful addition to the fisheries management toolkit.

Detecting Mediterranean White Sharks with Environmental DNA - Jeremy Jenrette; Jennifer Jenrette; Kobun Truelove; Stefano Moro; Nick Dunn; Taylor Chapple; Austin Gallagher; Chiara Gambardella; Robert Schallert; Brendan Shea; David Curnick; Barbara Block; et al. (Oceanography, 2023)
The white shark (Carcharodon carcharias) is a globally distributed, ecologically important top predator whose biology and population dynamics are challenging to study. Basic biological parameters remain virtually unknown in the Mediterranean Sea due to its historically low population density, dwindling population size, and lack of substantial sightings. White sharks are considered Critically Endangered in the Mediterranean Sea, and recent analyses suggest that the population has declined by 52% to 96% from historical levels in different Mediterranean sectors (Moro et al., 2020). Thus, white shark sightings dating back to 1860 are being used to estimate population trajectories throughout the entire region. Though the population size is unknown, remaining individuals are thought to be primarily restricted to a handful of hotspots deemed important for their reproduction and foraging. One of these hypothesized hotspots is the Sicilian Channel, which accounts for 19% of total historical sightings.

Informing Management of Atlantic Bluefin Tuna Using Telemetry Data - Rebecca Whitlock; Robert J. Schallert; Michael J. W. Stokesbury; Michael Castleton; Barbara A. Block (Frontiers in Marine Science, 2022)
Sustainable management of exploited marine fish and wildlife populations requires knowledge about their productivity. Survival from natural causes of mortality is a key component of population productivity, but is notoriously difficult to estimate. We evaluate the potential for acoustic telemetry as a long-term monitoring tool to estimate rates of natural mortality. We present a Bayesian multistate mark-recapture model for telemetry data collected over a decade from 188 Atlantic bluefin tuna ( Thunnus thynnus) and apply it to estimate the rate of natural mortality using only acoustic tag detections for all animals, or using acoustic tag detections for 96 single-tagged tuna plus acoustic tag detections combined with estimated positions from pop-up satellite archival tags for 92 double-tagged animals. We support the model for bluefin tuna with a simulation study to quantify bias in estimates of population dynamics parameters and investigate the effect of auxiliary information from satellite tagging on mortality rate estimates for different acoustic tag detection probability scenarios. We obtained posterior estimates of the instantaneous annual natural mortality (survival) rate across a decade of tagging for Atlantic bluefin tuna of 0.17 yr -1 (0.84 yr -1 ) both using only acoustic tagging data, and using a combination of acoustic and satellite tagging data. Use of a prior implying a higher rate of fishing mortality yielded an instantaneous annual natural mortality (survival) estimate of 0.10 yr -1 (0.90 yr -1 ), with combined acoustic and satellite tag data. Results from the simulation study indicate that the use of satellite tags can improve the precision and accuracy of estimates of detection probabilities, area-specific movement probabilities and mortality rates, where the extent of the improvement depends on true underlying acoustic tag detection probabilities. Our work demonstrates that long-term acoustic tagging data sets have strong potential for monitoring of highly migratory marine fish and wildlife populations, providing information on a number of key parameters, including survival and movement rates. However, improved information on tag reporting rates or fishing mortality is needed to better separate natural and fisheries mortality for Atlantic bluefin tuna.

Mismatches in scale between highly mobile marine megafauna and marine protected areas - Melinda G. Conners; Nicholas B. Sisson; Pierre D. Agamboue; Philip W. Atkinson; Alastair M. M. Baylis; Scott R. Benson; Barbara A. Block; Steven J. Bograd; Pablo Bordino; W. D. Bowen; Paul Brickle; Ignacio M. Bruno; et al. (Frontiers in Marine Science, 2022)
Marine protected areas (MPAs), particularly large MPAs, are increasing in number and size around the globe in part to facilitate the conservation of marine megafauna under the assumption that large-scale MPAs better align with vagile life histories; however, this alignment is not well established. Using a global tracking dataset from 36 species across five taxa, chosen to reflect the span of home range size in highly mobile marine megafauna, we show most MPAs are too small to encompass complete home ranges of most species. Based on size alone, 40% of existing MPAs could encompass the home ranges of the smallest ranged species, while only < 1% of existing MPAs could encompass those of the largest ranged species. Further, where home ranges and MPAs overlapped in real geographic space, MPAs encompassed < 5% of core areas used by all species. Despite most home ranges of mobile marine megafauna being much larger than existing MPAs, we demonstrate how benefits from MPAs are still likely to accrue by targeting seasonal aggregations and critical life history stages and through other management techniques.

Global-Scale Environmental Niche and Habitat of Blue Shark (Prionace glauca) by Size and Sex: A Pivotal Step to Improving Stock Management - Jean-Noël Druon; Steven Campana; Frederic Vandeperre; Fábio H. V. Hazin; Heather Bowlby; Rui Coelho; Nuno Queiroz; Fabrizio Serena; Francisco Abascal; Dimitrios Damalas; Michael Musyl; Jon Lopez; et al. (Frontiers in Marine Science, 2022)
Blue shark ( Prionace glauca ) is amongst the most abundant shark species in international trade, however this highly migratory species has little effective management and the need for spatio-temporal strategies increases, possibly involving the most vulnerable stage or sex classes. We combined 265,595 blue shark observations (capture or satellite tag) with environmental data to present the first global-scale analysis of species’ habitat preferences for five size and sex classes (small juveniles, large juvenile males and females, adult males and females). We leveraged the understanding of blue shark biotic environmental associations to develop two indicators of foraging location: productivity fronts in mesotrophic areas and mesopelagic micronekton in oligotrophic environments. Temperature (at surface and mixed layer depth plus 100 m) and sea surface height anomaly were used to exclude unsuitable abiotic environments. To capture the horizontal and vertical extent of thermal habitat for the blue shark, we defined the temperature niche relative to both sea surface temperature ( SST ) and the temperature 100 m below the mixed layer depth ( T mld+100 ). We show that the lifetime foraging niche incorporates highly diverse biotic and abiotic conditions: the blue shark tends to shift from mesotrophic and temperate surface waters during juvenile stages to more oligotrophic and warm surface waters for adults. However, low productivity limits all classes of blue shark habitat in the tropical western North Atlantic, and both low productivity and warm temperatures limit habitat in most of the equatorial Indian Ocean (except for the adult males) and tropical eastern Pacific. Large females tend to have greater habitat overlap with small juveniles than large males, more defined by temperature than productivity preferences. In particular, large juvenile females tend to extend their range into higher latitudes than large males, likely due to greater tolerance to relatively cold waters. Large juvenile and adult females also seem to avoid areas with intermediate SST (~21.7-24.0°C), resulting in separation from large males mostly in the tropical and temperate latitudes in the cold and warm seasons, respectively. The habitat requirements of sensitive size- and sex-specific stages to blue shark population dynamics are essential in management to improve conservation of this near-threatened species.

Risk and Reward in Foraging Migrations of North Pacific Albacore Determined From Estimates of Energy Intake and Movement Costs - Barbara A. Muhling; Stephanie Snyder; Elliott L. Hazen; Rebecca E. Whitlock; Heidi Dewar; Jong-Yeon Park; Charles A. Stock; Barbara A. Block (Frontiers in Marine Science, 2022)
North Pacific albacore ( Thunnus alalunga ) is a commercially important tuna species known to undertake extensive migratory movements between nearshore waters of the California Current and offshore environments in the central Pacific. However, these migration behaviors are highly variable, with some individuals traveling thousands of kilometers within a season, and others largely resident in the southern California Current throughout the year. In this study, we use data from 33 archival-tagged albacore (released between 2003 and 2011) to examine the movements, physiology and ecology of tuna following different migratory pathways. We used direct measurements of body temperature and ambient water temperature from internal archival tags to estimate energy intake via the Heat Increment of Feeding (HIF), the increased internal heat production associated with digestion of a meal. Our results indicate that HIF was variable in space and time, but it was highest for individuals foraging in the offshore North Pacific Transition Zone and southern California Current during spring and summer, and lowest in the Transition Zone in fall. None of the migratory strategies examined appeared to confer consistently higher energetic benefits than the others. Fish remaining resident in the southern California Current year-round incurred lower migration costs, and could access favorable foraging conditions off Baja California in spring and summer. In contrast, fish which undertook longer migrations had much higher energetic costs during periods of faster transit times, but were able to reach highly productive foraging areas in the central and western Pacific. HIF was generally higher in larger fish, and when ambient temperatures were cooler, but was not strongly correlated with other environmental covariates. Our analyses offer new avenues for studying the physiology of wild tuna populations, and can complement diet and isotopic studies to further understanding of fish ecology.

Multi-Decadal High-Resolution Data Reveal the Cryptic Vertical Movement Patterns of a Large Marine Predator Along the Californian Coast - Samantha Andrzejaczek; Taylor K. Chapple; Salvador J. Jorgensen; Scot D. Anderson; Michael Castleton; Paul E. Kanive; Timothy D. White; Barbara A. Block (Frontiers in Marine Science, 2022)
Over the last two decades, satellite tagging of adult and sub-adult white sharks Carcharodon carcharias off the west coast of North America has revealed a predictable onshore-offshore migratory cycle. Our current understanding of the vertical movements exhibited by white sharks while in their coastal foraging phase in the California Current, however, remains limited. Here, we used recovered datasets from 31 archival satellite tags to quantify vertical habitat use. Tags were deployed on individuals between 2000 and 2018 and recorded depth and temperature data at continuous 1–120 s intervals before being recovered up to a year after deployments. Four satellite-tagged individuals were concurrently tagged with acoustic tags, providing precise location data when detected by acoustic receivers that allowed us to explore how reported vertical habitat use varied spatially. While in the coastal shelf waters, white sharks moved at a mean depth ± SD of 14.3 ± 4.0 m and occupied significantly deeper depths during the day than the night. High individual, temporal and spatial variation was evident in vertical movements, while consistent diel and lunar effects emphasized the importance of light-level driving vertical behavior around hunting sites. The vertical movement behaviors reported here provide knowledge of how white sharks may directly and indirectly interact with their mammalian prey in a dynamic three-dimensional system during their capital foraging phase. Temporal patterns in vertical behavior, for instance, indicated that surface waters during early morning hours are the riskiest place for prey. Combining these novel findings with higher-resolution biologging techniques in future studies will allow us to further contextualize fine-scale vertical movement behaviors of white sharks and examine the specific foraging events that could not yet be isolated in the tagging data.

Movescapes and eco‐evolutionary movement strategies in marine fish: Assessing a connectivity hotspot - Susan K. Lowerre‐Barbieri; Claudia Friess; Lucas P. Griffin; Danielle Morley; Gregory B. Skomal; Joel W. Bickford; Neil Hammerschlag; Mitchell J. Rider; Matthew J. Smukall; Maurits P. M. van Zinnicq Bergmann; Tristan L. Guttridge; Andrea M. Kroetz; et al. (Fish and Fisheries, 2021)
Data from the Integrated Tracking of Aquatic Animals in the Gulf of Mexico (iTAG) network, and sister networks, were used to evaluate fish movements in the Florida Keys—an extensive reef fish ecosystem just north of Cuba connecting the Atlantic Ocean and Gulf of Mexico. We analysed ~2 million detections for 23 species, ranging from reef fish such as Nassau grouper ( Epinephelus striatus , Serranidae) to migratory apex predators such as white sharks ( Carcharodon carcharias , Lamnidae). To facilitate comparisons across species, we used an eco‐evolutionary movement strategy framework that identified measurable movement traits and their proximate and ultimate drivers. Detectability was species‐specific and quantified with a detection potential index. Life stages detected in the study area varied by species and residency varied with life stage. Four annual movement types were identified as follows: high site‐fidelity residents, range residents, seasonal migrants and general migrants. The endangered smalltooth sawfish ( Pristis pectinata , Pristidae), a seasonal migrant, exhibited the greatest within‐ecosystem connectivity. Site attachment, stopover and deep‐water migration behaviours differed between individuals, species and annual movement types. All apex predators were migratory. General migrants were significantly larger than fish in the other movement types, a life‐history and movement trait combination that is common but not exclusive, as many small pelagics also migrate. Most teleosts exhibited movements associated with spawning. As concerns grow over habitat and biodiversity loss, multispecies movescapes, such as presented here, are expected to play an increasingly important role in informing ecosystem‐based and non‐extractive fisheries management strategies.

Yellowfin Tuna Behavioural Ecology and Catchability in the South Atlantic: The Right Place at the Right Time (and Depth) - Serena R. Wright; David Righton; Joachim Naulaerts; Robert J. Schallert; Chris A. Griffiths; Taylor Chapple; Daniel Madigan; Vladimir Laptikhovsky; Victoria Bendall; Rhys Hobbs; Doug Beare; Elizabeth Clingham; et al. (Frontiers in Marine Science, 2021)
The yellowfin tuna ( Thunnus albacares: YFT) is a widely distributed, migratory species that supports valuable commercial fisheries. Landings of YFT are seasonally and spatially variable, reflecting changes in their availability and accessibility to different fleets and metiers which, in turn, has implications for sustainable management. Understanding the dynamics of YFT behaviour and how it is affected by biological and ecological factors is therefore of consequence to fisheries management design. Archival and pop-up satellite tags (PSAT) were used in the South Atlantic Ocean around St Helena between 2015 and 2020 to collect information on the movements, foraging and locomotory behaviour of YFT. The study aimed to (1) identify vertical behaviour of YFT within St Helena’s EEZ; (2) assess the timing and depth of potential feeding events and (3) to use the information to inform on the catchability of YFT to the local pole and line fishing fleet. Results indicate that the YFT daytime behaviour shifted between shallow with high incidence of fast starts in surface waters in summer months (December to April), to deep with high incidence of strikes at depth in colder months (May to November). Catchability of YFT was significantly reduced between May and November as YFT spent more time at depths below 100 m during the day, which coincides with a reduction in the quantity of YFT caught by the inshore fleet.

Behavior and Ecology of Silky Sharks Around the Chagos Archipelago and Evidence of Indian Ocean Wide Movement - David J. Curnick; Samantha Andrzejaczek; David M. P. Jacoby; Daniel M. Coffey; Aaron B. Carlisle; Taylor K. Chapple; Francesco Ferretti; Robert J. Schallert; Timothy White; Barbara A. Block; Heather J. Koldewey; Ben Collen (Frontiers in Marine Science, 2020)
Silky sharks ( Carcharhinus falciformis ) represent a major component of global shark catch, both directly and as bycatch, and populations are declining as a result. An improved understanding of their movement ecology is needed to support conservation efforts. We deployed satellite and acoustic tags (2013–2018) and analyzed historical fisheries records (1997–2009), to investigate the spatial ecology of silky sharks in the central Indian Ocean and a large Marine Protected Area (MPA; 640,000 km 2 ) around the Chagos Archipelago. We observed high fidelity to the MPA, and a sustained diurnal association with a seamount complex, with individuals moving off at night and returning at sunrise. Yet, we also observed large-scale divergent movements in two satellite tagged individuals and documented the furthest recorded displacement distance for a satellite tagged silky shark to date, with one individual moving from the MPA to the Kenyan coast—a displacement distance of 3,549 km (track distance ∼4,782 km). Silky sharks undertook diel vertical migrations and oscillatory diving behavior, spending > 99% of their time in the top 100 m, and diving to depths of greater than 300 m, overlapping directly with typical deployments of purse seine and longline sets in the Indian Ocean. One individual was recorded to a depth of 1,112 m, the deepest recorded silky shark dive to date. Individuals spent 96% of their time at liberty within water temperatures between 24 and 30°C. Historic fisheries data revealed that silky sharks were a major component of the shark community around the archipelago, representing 13.69% of all sharks caught by longlines before the fishery closed in 2010. Over half (55.88%) of all individuals caught by longlines and purse seiners were juveniles. The large proportion of juveniles, coupled with the high site fidelity and residence observed in some individuals, suggests that the MPA could provide considerable conservation benefits for silky sharks, particularly during early life-history stages. However, their high mobility potential necessitates that large MPAs need to be considered in conjunction with fisheries regulations and conservation measures in adjacent EEZs and in areas beyond national jurisdiction.

Tracking the response of industrial fishing fleets to large marine protected areas in the Pacific Ocean - Timothy D. White; Tiffany Ong; Francesco Ferretti; Barbara A. Block; Douglas J. McCauley; Fiorenza Micheli; Giulio A. De Leo (Conservation Biology, 2020)
Large marine protected areas (MPAs) of unprecedented size have recently been established across the global oceans, yet their ability to meet conservation objectives is debated. Key areas of debate include uncertainty over nations’ abilities to enforce fishing bans across vast, remote regions and the intensity of human impacts before and after MPA implementation. We used a recently developed vessel tracking data set (produced using Automatic Identification System detections) to quantify the response of industrial fishing fleets to 5 of the largest MPAs established in the Pacific Ocean since 2013. After their implementation, all 5 MPAs successfully kept industrial fishing effort exceptionally low. Detected fishing effort was already low in 4 of the 5 large MPAs prior to MPA implementation, particularly relative to nearby regions that did not receive formal protection. Our results suggest that these large MPAs may present major conservation opportunities in relatively intact ecosystems with low immediate impact to industrial fisheries, but the large MPAs we considered often did not significantly reduce fishing effort because baseline fishing was typically low. It is yet to be determined how large MPAs may shape global ocean conservation in the future if the footprint of human influence continues to expand. Continued improvement in understanding of how large MPAs interact with industrial fisheries is a crucial step toward defining their role in global ocean management.

A review of a decade of lessons from one of the world’s largest MPAs: conservation gains and key challenges - Graeme C. Hays; Heather J. Koldewey; Samantha Andrzejaczek; Martin J. Attrill; Shanta Barley; Daniel T. I. Bayley; Cassandra E. Benkwitt; Barbara Block; Robert J. Schallert; Aaron B. Carlisle; Pete Carr; Taylor K. Chapple; et al. (Marine Biology, 2020)

Abundance and distribution of the white shark in the Mediterranean Sea - Stefano Moro; Giovanna Jona‐Lasinio; Barbara Block; Fiorenza Micheli; Giulio De Leo; Fabrizio Serena; Massimiliano Bottaro; Umberto Scacco; Francesco Ferretti (Fish and Fisheries, 2020)
Conservation of apex predators is a key challenge both in marine and terrestrial ecosystems. The white shark is a rare but persistent inhabitant of the Mediterranean Sea and it is currently assessed as “critically endangered” in the region. However, the population trends and dynamics of this species in the area are still unknown. Little is known about white shark distribution, habitat use and population abundance trends, aspects that are critical for conservation and management. In this study, we built the most comprehensive database of white shark occurrence records in the region. We collected 773 different records from different sources and used them to characterize the spatial and temporal patterns of abundance of Mediterranean white sharks between 1860 and 2016. We analysed these data by using generalized additive models and used spatially disaggregated information on human population abundance as a proxy of observation effort. Our results suggest a complex trajectory of population change characterized by a historical increase and a more recent reduction (61%, range 58%–72%) since the second half of the 20th century. In particular, analyses reveal a 52% (range 37%–88%) to 96% (range 92%–100%) overall decline in different Mediterranean sectors and a contraction in spatial distribution. Here, we provide the first reconstruction of abundance trends and offer new hypotheses regarding the drivers of change of white sharks in the Mediterranean. Our approach can be broadly applied to data‐poor contexts to reconstruct change and inform the conservation of endangered top predators in the Mediterranean Sea and other intensely used marine regions.

Animal-Borne Telemetry: An Integral Component of the Ocean Observing Toolkit - Rob Harcourt; Ana M. M. Sequeira; Xuelei Zhang; Fabien Roquet; Kosei Komatsu; Michelle Heupel; Clive McMahon; Fred Whoriskey; Mark Meekan; Gemma Carroll; Stephanie Brodie; Colin Simpfendorfer; et al. (Frontiers in Marine Science, 2019)

Estimating Space Use of Mobile Fishes in a Large Marine Protected Area With Methodological Considerations in Acoustic Array Design - Aaron B. Carlisle; David Tickler; Jonathan J. Dale; Francesco Ferretti; David J. Curnick; Taylor K. Chapple; Robert J. Schallert; Michael Castleton; Barbara A. Block (Frontiers in Marine Science, 2019)

Movements and dive behavior of juvenile California sea lions from Año Nuevo Island - Elizabeth A. McHuron; Barbara A. Block; Daniel P. Costa (Marine Mammal Science, 2018)

Ocean Observations Using Tagged Animals - Fabien Roquet; Lars Boehme; Mike Fedak; Barbara Block; Jean-Benoit Charrassin; Daniel Costa; Luis Hückstädt; Christophe Guinet; Robert Harcourt; Mark Hindell; Clive McMahon; Bill Woodward (Oceanography, 2017)

Influence of temperature and oxygen on the distribution of blue marlin ( Makaira nigricans ) in the Central Pacific - Aaron B. Carlisle; Randall E. Kochevar; Martin C. Arostegui; James E. Ganong; Michael Castleton; Jason Schratwieser; Barbara A. Block (Fisheries Oceanography, 2017)
The blue marlin ( Makaira nigricans ) is a highly migratory pelagic predator of tropical and subtropical seas. Information on the habitat use of marine species is fundamental to understanding their ecology and population dynamics and is needed to inform responsible management strategies. Using a long‐term satellite tagging data set from The International Game Fish Association Great Marlin Race, we examined habitat use and how oxygen and temperature influence the horizontal and vertical distributions of blue marlin in the Central Pacific. Blue marlin primarily occurred in warm waters (26–30°C) and exhibited a diel bimodal depth distribution across the 5‐year data record (2009–2013), with fish spending the majority of their time near the surface at night and at deeper depths during the day (25–100 m). The depth distribution of blue marlin was limited in areas where low oxygen and/or temperature conditions occur closer to the surface, with the extent of habitat compression being greatest when both oxygen and temperature were limiting. The migrations of blue marlin appeared restricted during the 2010 La Niña, when increased equatorial upwelling resulted in an extension of the cold, low oxygen waters of the cold tongue into the Central Pacific, creating a barrier to the trans‐equatorial migrations that occurred during all other tagging years. If the frequency and intensity of La Niña events increases and the oxygen minimum layer continues to expand as has been predicted under certain climate change scenarios, the migratory behavior and habitat availability of blue marlin may be impacted.

Life in the open ocean: seasonal migration and diel diving behaviour of Southern Hemisphere porbeagle sharks (Lamna nasus) - Malcolm P. Francis; John C. Holdsworth; Barbara A. Block (Marine Biology, 2015)

Hearing thresholds of swimming Pacific bluefin tuna Thunnus orientalis - Jonathan J. Dale; Michael D. Gray; Arthur N. Popper; Peter H. Rogers; Barbara A. Block (Journal of Comparative Physiology A, 2015)

Estimating apparent survival of sub-adult and adult white sharks (Carcharodon carcharias) in central California using mark-recapture methods - Paul E. Kanive; Jay J. Rotella; Salvador J. Jorgensen; Taylor K. Chapple; Scot D. Anderson; A. Peter Klimley; Barbara A. Block (Frontiers in Marine Science, 2015)

Reconstructing transoceanic migration patterns of Pacific bluefin tuna using a chemical tracer toolbox - Daniel J. Madigan; Zofia Baumann; Aaron B. Carlisle; Danielle K. Hoen; Brian N. Popp; Heidi Dewar; Owyn E. Snodgrass; Barbara A. Block; Nicholas S. Fisher (Ecology, 2014)
Large pelagic predators play important roles in oceanic ecosystems, and may migrate vast distances to utilize resources in different marine ecoregions. Understanding movement patterns of migratory marine animals is critical for effective management, but often challenging, due to the cryptic habitat of pelagic migrators and the difficulty of assessing past movements. Chemical tracers can partially circumvent these challenges by reconstructing recent migration patterns. Pacific bluefin tuna ( Thunnus orientalis ; PBFT) inhabit the western and eastern Pacific Ocean, and are in steep decline due to overfishing. Understanding age‐specific eastward transpacific migration patterns can improve management practices, but these migratory dynamics remain largely unquantified. Here, we combine a Fukushima‐derived radiotracer ( 134 Cs) with bulk tissue and amino acid stable isotope analyses of PBFT to distinguish recent migrants from residents of the eastern Pacific Ocean. The proportion of recent migrants to residents decreased in older year classes, though the proportion of older PBFT that recently migrated across the Pacific was greater than previous estimates. This novel toolbox of biogeochemical tracers can be applied to any species that crosses the North Pacific Ocean.

Archival and acoustic tags reveal the post-spawning migrations, diving behavior, and thermal habitat of hatchery-origin Sacramento River steelhead kelts (Oncorhynchus mykiss) - Steven L. H. Teo; Phil T. Sandstrom; Eric D. Chapman; Robert E. Null; Kurt Brown; A. Peter Klimley; Barbara A. Block (Environmental Biology of Fishes, 2013)

The role of discounting and dynamics in determining the economic efficiency of time-area closures for managing fishery bycatch - Paul R. Armsworth; Barbara A. Block; Josh Eagle; Joan E. Roughgarden (Theoretical Ecology, 2011)

Long-term individual identification and site fidelity of white sharks, Carcharodon carcharias, off California using dorsal fins - Scot D. Anderson; Taylor K. Chapple; Salvador J. Jorgensen; A. Peter Klimley; Barbara A. Block (Marine Biology, 2011)

Heterologous hybridization to a complementary DNA microarray reveals the effect of thermal acclimation in the endothermic bluefin tuna ( Thunnus orientalis ) - PEDRO C. CASTILHO; BRADLEY A. BUCKLEY; GEORGE SOMERO; BARBARA A. BLOCK (Molecular Ecology, 2009)
The temperature stress that pelagic fishes experience can induce physiological and behavioural changes that leave a signature in gene expression profiles. We used a functional genomics approach to identify genes that were up‐ or down‐regulated following thermal stress in the Pacific bluefin tuna. Following the acclimation period, 113, 81 and 196 genes were found to be differentially expressed between the control (20 °C) and cold (15°) treatment groups, in ventricle, red muscle and white muscle, respectively. The genes whose expression levels were responsive to thermal acclimation varied according to muscle fibre type, perhaps reflecting the tissue‐specific degrees of endothermy characteristic of this species.

Advances in Conservation Oceanography: New Tagging and Tracking Technologies and Their Potential for Transforming the Science Underlying Fisheries Management - Charles Greene; Barbara Block; David Welch; George Jackson; Gareth Lawson; Erin Rechisky (Oceanography, 2009)

Near real time satellite tracking of striped marlin (Kajikia audax) movements in the Pacific Ocean - John C. Holdsworth; Tim J. Sippel; Barbara A. Block (Marine Biology, 2009)

Mitochondrial DNA and electronic tracking reveal population structure of Atlantic bluefin tuna (Thunnus thynnus) - Andre M. Boustany; Carol A. Reeb; Barbara A. Block (Marine Biology, 2008)

Ultrastructure of the sarcoplasmic reticulum in cardiac myocytes from Pacific bluefin tuna - Alessandro Di Maio; Barbara A. Block (Cell and Tissue Research, 2008)

Oceanographic preferences of Atlantic bluefin tuna, Thunnus thynnus, on their Gulf of Mexico breeding grounds - Steven L. H. Teo; Andre M. Boustany; Barbara A. Block (Marine Biology, 2007)

Migration and habitat of white sharks (Carcharodon carcharias) in the eastern Pacific Ocean - Kevin C. Weng; Andre M. Boustany; Peter Pyle; Scot D. Anderson; Adam Brown; Barbara A. Block (Marine Biology, 2007)

Movements, behavior, and habitat utilization of yellowfin tuna (Thunnus albacares) in the northeastern Pacific Ocean, ascertained through archival tag data - Kurt M. Schaefer; Daniel W. Fuller; Barbara A. Block (Marine Biology, 2007)

Horizontal and vertical movements of juvenile bluefin tuna ( Thunnus orientalis ) in relation to seasons and oceanographic conditions in the eastern Pacific Ocean - TAKASHI KITAGAWA; ANDRE M. BOUSTANY; CHARLES J. FARWELL; THOMAS D. WILLIAMS; MICHAEL R. CASTLETON; BARBARA A. BLOCK (Fisheries Oceanography, 2007)
Electronically tagged juvenile Pacific bluefin, Thunnus orientalis , were released off Baja California in the summer of 2002. Time‐series data were analyzed for 18 fish that provided a record of 380 ± 120 days (mean ± SD) of ambient water and peritoneal cavity temperatures at 120 s intervals. Geolocations of tagged fish were estimated based on light‐based longitude and sea surface temperature‐based latitude algorithms. The horizontal and vertical movement patterns of Pacific bluefin were examined in relation to oceanographic conditions and the occurrence of feeding events inferred from thermal fluctuations in the peritoneal cavity. In summer, fish were located primarily in the Southern California Bight and over the continental shelf of Baja California, where juvenile Pacific bluefin use the top of the water column, undertaking occasional, brief forays to depths below the thermocline. In autumn, bluefin migrated north to the waters off the Central California coast when thermal fronts form as the result of weakened equatorward wind stress. An examination of ambient and peritoneal temperatures revealed that bluefin tuna fed during this period along the frontal boundaries. In mid‐winter, the bluefin returned to the Southern California Bight possibly because of strong downwelling and depletion of prey species off the Central California waters. The elevation of the mean peritoneal cavity temperature above the mean ambient water temperature increased as ambient water temperature decreased. The ability of juvenile bluefin tuna to maintain a thermal excess of 10°C occurred at ambient temperatures of 11–14°C when the fish were off the Central California coast. This suggests that the bluefin maintain peritoneal temperature by increasing heat conservation and possibly by increasing internal heat production when in cooler waters. For all of the Pacific bluefin tuna, there was a significant correlation between their mean nighttime depth and the visible disk area of the moon.

Striped marlin ( Tetrapturus audax ) movements and habitat utilization during a summer and autumn in the Southwest Pacific Ocean - TIM J. SIPPEL; PETER S. DAVIE; JOHN C. HOLDSWORTH; BARBARA A. BLOCK (Fisheries Oceanography, 2007)
Six striped marlin ( Tetrapturus audax ) were caught on hook and line from recreational fishing boats near northern New Zealand (34°S, 174°E) and tagged and released with pop‐off satellite archival tags. For periods ranging from 22 to 60 days over the geographical range 168°E–170°W and 13–34°S, five tags collected a total of 202 days (range of 21–60 days) of data. These data permit the investigation of striped marlin geographical and vertical movements and water temperatures occupied from February to June 2003. One hundred and one days of geoposition data showed a preliminary view of their movements in and around New Zealand waters. Transmitted temperature and depth data indicated striped marlin spent 80% (±2%) of their time in the mixed layer including 72% (±2%) of their time in the top 5 m. Temperature data indicated 75% (±10%) of the striped marlin’s time was spent in water temperatures between 20.1 and 24.0°C. Tagged striped marlin moved faster during periods of directed movement away from New Zealand versus periods of passive movements when the fish were proximal to New Zealand or not moving in any specific direction. These data support some existing hypotheses about striped marlin physiological ecology and allow preliminary suggestions about how striped marlin bycatch might be reduced.

Results of satellite tagging of Atlantic bluefin tuna, Thunnus thynnus, off the coast of Ireland - Michael J. W. Stokesbury; Ronan Cosgrove; Andre Boustany; Daragh Browne; Steven L. H. Teo; Ronald K. O’Dor; Barbara A. Block (Hydrobiologia, 2007)

High apex predator biomass on remote Pacific islands - Charlotte Stevenson; Laure S. Katz; Fiorenza Micheli; Barbara Block; Kimberly W. Heiman; Chris Perle; Kevin Weng; Robert Dunbar; Jan Witting (Coral Reefs, 2007)

Annual migrations, diving behavior, and thermal biology of Atlantic bluefin tuna, Thunnus thynnus, on their Gulf of Mexico breeding grounds - Steven L. H. Teo; Andre Boustany; Heidi Dewar; Michael J. W. Stokesbury; Kevin C. Weng; Shana Beemer; Andrew C. Seitz; Charles J. Farwell; Eric D. Prince; Barbara A. Block (Marine Biology, 2007)

Movement and environmental preferences of Greenland sharks (Somniosus microcephalus) electronically tagged in the St. Lawrence Estuary, Canada - Michael J. W. Stokesbury; Chris Harvey-Clark; Jeffrey Gallant; Barbara A. Block; Ransom A. Myers (Marine Biology, 2005)

Comparison of light- and SST-based geolocation with satellite telemetry in free-ranging albatrosses - Scott A. Shaffer; Yann Tremblay; Jill A. Awkerman; R. William Henry; Steven L. H. Teo; David J. Anderson; Donald A. Croll; Barbara A. Block; Daniel P. Costa (Marine Biology, 2005)

Depth and muscle temperature of Pacific bluefin tuna examined with acoustic and pop-up satellite archival tags - David J. Marcinek; Susanna B. Blackwell; Heidi Dewar; Ellen V. Freund; Charles Farwell; Daniel Dau; Andrew C. Seitz; Barbara A. Block (Marine Biology, 2001)